Irida-graphene as a high-performance anode for sodium batteries - Martins, Nicolas F. [UNESP]; Laranjeira, José A. [UNESP]; Fabris, Guilherme S.L.; Denis, Pablo A.; Sambrano, Julio R. [UNESP] (Elsevier, 2024)
Clean energy storage is in the spotlight of the scientific community, as is the development of alternatives to the negative impact of conventional lithium-based batteries; therefore, sodium-ion batteries (SIBs) have emerged due to the abundant Na resources. In this sense, the performance of irida-graphene (IG), a 2D carbon allotrope with metallic character, and geometrically formed by 3-, 6- and 8- carbon rings, is computationally investigated for Na storage by density functional theory (DFT) simulations. The maximum Na capacity in the IG is 24 atoms, a ratio of 1 Na to 2C (1:2), with adsorption energies from −1.42 eV (single Na) to −0.38 eV (24 Na), demonstrating its electrochemical stability. The Na mobility was analyzed, indicating a high diffusion rate (3.11 × 10−5 cm2/s at 300 K) associated with a very small diffusion barrier (0.09 eV). The operating open circuit voltage (OCV) ranges from 0.32 to 1.42 V, which is suitable for a safety battery application. Finally, the Na storage capacity is 1022 mAhg−1, surpassing many commercial anodes and competitive with other structures. The results highlight the IG potential as an effective and safe anode material for SIBs.
Keywords: 2D materials; Battery; DFT; Irida-graphene; SIBs; 2d material; Clean energy; Density-functional-theory; Graphenes; High-performance anodes; Scientific community; Sodium battery; Sodium ion batteries